“EKONOMI ISLAM UNTUK KEADILAN SOSIAL DAN KESEJAHTERAAN, CUPLIKAN DARI SEJARAH HIDUP NABI MUHAMMAD SAW”: "ISLAMIC ECONOMICS FOR SOCIAL JUSTICE AND WELFARE, AN EXCERPT FROM THE LIFE HISTORY OF THE PROPHET MUHAMMAD SAW" - Oria, Ehsanullah; oria, Hafizullah; Susanta, Hari; Wijayanto, Andi (Jurnal Istiqro, 2024)
In the past two decades, there has been a significant global growth in Islamic banking and finance, drawing attention to the importance of Islamic economics. While various studies have explored Islamic economics using different methods, there's still a shortage of research focusing on the economic aspects from the life and teachings of Prophet Muhammad SAW. In practice, Prophet Muhammad SAW implemented economic and political policies that played a crucial role in creating a fair, stable, and prosperous society. He established the foundational principles of an Islamic economy, including the precursor to a federal reserve known as Baitul Maal and introduced a currency to combat inflation. He actively fought against corruption and interest-based transactions (riba) and encouraged creativity and innovation within the Muslim community (Ummah) in various industries and global trade. This paper takes a historical approach to uncover the fundamental concepts of Islamic economics introduced by Prophet Muhammad SAW during his time in Madinah, emphasizing social justice and societal well-being.